USING NUMBERED HEAD TOGETHER LEARNING MODEL TO IMPROVE STUDENTS' VOCABULARY - Hamise, Nevie K.D; Mogea, Tini; Tuna, Jim Ronny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The learning process that is carried out in a monotonous way turns out to result in low student absorption of knowledge. Students have many problems, especially lack of vocabulary. This research is aimed to find out whether using Numbered Head Together there is an improvement for students who have problem of lack vocabulary or not. In this research was quantitative research used pre-experimental design with one group of pre-test and post-test. The subject of the study was conducted at SMP NEGERI 2 ERIS which consisted of 18 students. Then, the technique of collecting the data is through pre-test and post-test. The results of this research were as follows: Pre-test, where the writer has not used the Numbered Head Together Learning Model, as a result there is only 1 student who got the highest score was 8 or 11%, with a mean value of 5.2. And for the post-test, the writer has implemented the Numbered Head Together Learning Model, with an average value of 7.16. From the results above, the mean score of the post-test is highest than the mean score of the pre-test. Thus, the final conclusion that the writer to convey is that Using Numbered Head Together Learning Model is able to improve students' vocabulary.